Influence of the marketing mix on the decision to purchase Oepet Oe cigarette products in the people of Pamekasan district - Uki Yonda Asepta (Central Research Institute for Agriculture (CeRIA), 2022)
The purpose of this research is to analyze the significant effect simultaneously of the marketing mix on the purchasing decision of Oepet Oe cigarettes. purchasing decisions for Oepet Oe cigarettes. Companies that are able to demonstrate effective performance will be able to face competitive conditions between industrial environments. The condition of the business environment that continues to develop with a high level of competition requires companies to be able to overcome the impact of these changes on the company's future. To be able to face a competitive level of competition, companies need to develop and apply competitive advantage on an ongoing basis, for this reason there must be careful planning by taking into account the company's industrial (internal and external) environmental factors. The results of this study aim to find out how the consumer's response or consumer's decision to purchase an item is seen from the way the marketing is done so that customers have an attraction to these commodities both by planning and promotion carried out, therefore the method used in this research is the survey method. . According to Singarimbun and Effendi (1995: 3) survey research is research that takes a sample from a population and uses a questionnaire as a data collection tool with the main sample in this study being consumers of these goods.